Influence of Sowing Date on Growth and Yield Components of Sunflower (Helianthus Annuus L.) in Semi-Arid Zone - D. Abu Anga, Hilwa,; A. Marajan, Wael; backer H. Mohammed, Abu; Eldin M. Idris, Baha (Journal of Agronomy Research, 2019)
The main objective of this study was to quantify the influence of sowing date on growth and yield components of hybrid sunflower (Hysun33) cultivar in semi-arid zone. This experiment was conducted during the seasons 2014/2015-2015/2016 at the farm of the College of Agricultural Studies, Sudan University of Science and Technology, Shambat, Khartoum- Sudan. The experiment was arranged in randomized complete block design (RCBD) with four replications and three treatments. Different parameters were considered including plant height, leaf area index (LAI), filled sees number/head, head diameter, dry weight and yield components. The collected data were statistically analyzed. The results revealed that crop sown in May and July showed significant increase in plant height, LAI, head diameter, dry weight, field seed number/head, weight of 100 seeds; yield; and yield components; compared to crop sown in March. However, crop sown in the second season showed an increase in growth and yield components compared to the crop of the first season.
Keywords: Sowing Date; Sunflower; Yield Components; Semi-Arid Zone; Leaf Area Index; Plant Growth